The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1353/csd.2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Food Acquisition Struggles in the Context of South Africa: The Fundamentals of Student Development

Abstract: This article situates food at the heart of the fundamentals of student development, based on qualitative case study research. Food acquisition and food-related struggles in the context of the South African university are examined. Three overarching themes emerged from the analysis of the data, and are discussed in detail: depletion of food funds, acquiring food on campus, and awareness of others’ food struggles. The findings suggest that students struggling to acquire food are dominated by food acquisition iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…This finding is of importance, as these key personnel are often the decision-makers at higher education institutions. However, there is often a disconnect, with many campus stakeholders assuming student needs are being met [33,34]. Furthermore, previous research has shown that students are skeptical of administrators' commitment to providing basic need resources for students [35], which makes it essential that these players are engaged and understand the impact on their campus to ensure the sustainability of programs on campus.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of importance, as these key personnel are often the decision-makers at higher education institutions. However, there is often a disconnect, with many campus stakeholders assuming student needs are being met [33,34]. Furthermore, previous research has shown that students are skeptical of administrators' commitment to providing basic need resources for students [35], which makes it essential that these players are engaged and understand the impact on their campus to ensure the sustainability of programs on campus.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of working on academic progression may vary depending on the number of hours worked, and the reason the student elects to work (Triventi, 2014). In South Africa, students from low socioeconomic groups who experience food and housing insecurity may increase their hours of work (Broton and Goldrick-Rab, 2017;Dominguez-Whitehead, 2015 which in turn may impede their academic success. Moreover, students from impoverished backgrounds who receive financial assistance are sometimes expected to redirect some of this funding to support their families (Mngomezulu et al, 2017).…”
Section: High Tuition Fees and Student Employmentmentioning
confidence: 99%
“…Their underpreparedness ranges from a lack of digital literacy skills (Leonard et al 2016), inadequate language competencies (Davie 2016;Pineteh 2014;PIRLS 2016) and a lack of critical thinking skills (Temel 2014) to practical issues such as financial problems, inadequate network connectivity and logistical issues (e.g. accommodation, nutrition and transport barriers; Subotzky & Prinsloo 2011:177;Whitehead 2015). Since the student protests started in 2015, the call for Africanisation and decolonisation is getting louder.…”
Section: Why Is Blended Learning Important For Higher Education?mentioning
confidence: 99%